Étude comparée de l’usage parenthétique des verbes épistémiques dans trois langues romanes - Gerda Haßler (Discours)
This paper studies the syntactic behavior of French, Spanish and Portuguese epistemic verbs, which can be used parenthetically in all of these languages, but with differences in frequency and in their typical use and position. A comparative, corpus-based approach is pursued to examine the syntactic behavior of epistemic verbs in these languages. In this diachronic study of the parenthetical usage of epistemic verbs, the question is asked whether grammaticalization occurred in which the verbs took on a status similar to that of adverbs. In a process of grammaticalization, new units appear whose meaning can no longer be deduced from the initial elements and which may have undergone a process of reduction or fusion. This is not the case for epistemic verbs. It is therefore proposed to consider the diachronic development of epistemic verbs as a case of pragmaticalization, which is confirmed by the case of French, since parenthetical uses can be observed in Old French texts. We seek to demonstrate the hypothesis that the frequency of parenthetical usage, long present in the system of the language, has been intensified by favorable pragmatic conditions.